Violation of Cooperative Principles and Its Connection to Logical Fallacies: Critical Discourse Analysis on the Third Debate of Indonesian President 2024 - Riyadi, Adriyan Kholid; Baharuddin, Baharuddin; Junaidi, Ahmad; Mahyuni , Mahyuni (Journal of Authentic Research, 2025)
This research examines the violation of Grice’s Cooperative Principles and its connection to Logical Fallacies in the Third Debate of the 2024 Indonesian Presidential Election through a qualitative descriptive method framed within Critical Discourse Analysis (CDA). Using the Miles and Huberman model which consists of data reduction, data display, and conclusion drawing the study analyzed debate transcripts and video recordings to identify linguistic patterns of manipulation. The findings revealed 13 maxim violations (7 relevance, 4 quantity, 2 quality) and 39 logical fallacies, with straw man, red herring, and appeal to emotion as the most dominant. These violations were not random but deliberate rhetorical strategies used to deflect criticism, obscure weak arguments, and appeal emotionally to voters. The originality of this research lies in its integration of Grice’s Cooperative Principles and logical fallacy theory within the CDA framework, offering a more holistic linguistic approach to understanding persuasion in political discourse. Unlike previous studies that treated maxim violations and fallacies separately, this study explicitly links the two, showing how pragmatic violations produce fallacious reasoning that shapes ideological narratives. Theoretically, it enriches sociolinguistic and CDA perspectives by explaining how language functions as an instrument of power and persuasion, while practically it provides insights for election organizers to improve debate moderation, for journalists to conduct more critical reporting, and for educators to enhance media literacy and critical thinking.